2017
DOI: 10.1097/mou.0000000000000412
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported outcome measures in urology

Abstract: PROMs are effective tools for characterizing symptom burden and health-related quality of life. With increasing clinical implementation, PROMs are playing an increasing role in patients' clinical decision-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 81 publications
0
29
0
3
Order By: Relevance
“…Another limitation is the definition of success after 12 and 24 months follow‐up. Patient‐reported outcomes are difficult to define, resulting in a wide variety of instruments to assess these . It has been shown that there is a high association between patient‐reported outcome measures of quality of health and bladder diaries in patients with overactive bladder .…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is the definition of success after 12 and 24 months follow‐up. Patient‐reported outcomes are difficult to define, resulting in a wide variety of instruments to assess these . It has been shown that there is a high association between patient‐reported outcome measures of quality of health and bladder diaries in patients with overactive bladder .…”
Section: Discussionmentioning
confidence: 99%
“…Implementation of PROMs has transitioned from being primarily descriptive in nature to producing actionable findings. 19 Healthcare policy-makers now rely on these measures to determine whether specific procedures are worthwhile supporting and to compare outcomes between institutions. 20 Our findings can be used to ensure adequate counselling about TTPM-biopsies and point to a need for strategies such as mpMRI and targeted biopsies to minimize harms of TTPM-biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Value based healthcare and PROMs and PREMs are also considered important in urology. However, PROMs and PREMs for urolithiasis fall behind [10]. To demonstrate: in 2010 there were 16 validated instruments for prostate cancer, 11 for benign prostate hyperplasia and 24 for urinary incontinence [4].…”
Section: Introductionmentioning
confidence: 99%